A comparative study on the expression, purification and functional characterization of human adiponectin in pichia pastoris and escherichia coli - Rothan, H.A.; Teh, S.H.; Haron, K.; Mohamed, Z. (2012)
Adiponectin is one of the most bioactive substances secreted by adipose tissue and is involved in the protection against metabolic syndrome, artherosclerosis and type II diabetes. Research into the use of adiponectin as a promising drug for metabolic syndromes requires production of this hormone in high quantities considering its molecular isoforms. The objective of this study is to produce recombinant human adiponectin by Pichia pastoris (P-ADP) as a cheap and convenient eukaryotic expression system for potential application in pharmaceutical therapy. For comparison, adiponectin was also expressed using the Escherichia coli (E-ADP) expression system. Adiponectin was constructed by overlap-extension PCR, and cloned in standard cloning vector and hosts. Recombinant expression vectors were cloned in the P. pastoris and E. coli host strains, respectively. SDS-PAGE and western blotting were used to detect and analyse expressed recombinant protein in both systems. Adiponectin was purified by affinity chromatography and quantified using the Bradford Assay. The results of this study indicated that P-ADP quantity (0.111 mg/mL) was higher than that of E-ADP (0.04 mg/mL) and both were produced in soluble form. However, P-ADP was able to form high molecular weights of adiponectin molecules, whilst E-ADP was not able to form isoforms higher than trimer. In addition, P-ADP was more active in lowering blood glucose compared with E-ADP. The two types of proteins were equally efficient and significantly decreased blood triglyceride and increased high density lipoprotein. We conclude that P. pastoris is able to produce high quantity of bioactive adiponectin for potential use in treatment of metabolic syndromes.